Method for synthesizing ammonia by catalysis through energy radiation

By using the plasmon effect on nanostructured catalysts and using optical radiation and/or thermal radiation to convert N2 and water into ammonia, the problem of the existing ammonia synthesis method requiring high temperature and high pressure is solved, and high efficiency and low energy consumption ammonia is achieved synthesis.

CN115667144BActive Publication Date: 2025-02-07BEIJING GUANGHE ORIGINAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202080100965.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-05-15
Publication Date
2025-02-07
Estimated Expiration
2040-05-15

AI Technical Summary

Technical Problem

The existing ammonia synthesis methods require high temperature and high pressure conditions, resulting in energy consumption and environmental pollution, and have low nitrogen fixation efficiency.

Method used

Using nanostructured catalysts, N2 and water are converted to ammonia by light and/or thermal radiation under mild conditions using the plasmon effect.

Benefits of technology

Efficient ammonia synthesis is achieved under normal temperature and pressure, with high yield and mild reaction conditions, reducing energy consumption and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HPA0000329567650000011
    Figure HPA0000329567650000011
  • Figure HPA0000329567650000012
    Figure HPA0000329567650000012
  • Figure HPA0000329567650000021
    Figure HPA0000329567650000021
Patent Text Reader

Abstract

The present invention provides a method for producing ammonia by energy radiation, the method comprising contacting a nanostructured catalyst with at least one nitrogen-containing source and at least one hydrogen-containing source, and irradiating the nanostructured catalyst, the nitrogen-containing source and the hydrogen-containing source with energy to produce ammonia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for synthesizing ammonia by catalysis through energy radiation, and belongs to the field of nitrogen fixation reaction. Background Art

[0002] Ammonia (NH3) is not only a widely used chemical raw material, but can also be used as a non-carbon-based energy carrier, which has important applications in human society. At present, the Haber ammonia synthesis process discovered in the 20th century is still widely used in industry. This process needs to be carried out under harsh conditions of high temperature and high pressure (over 100atm, over 300℃), which causes a lot of energy consumption and environmental pollution. It is imperative to develop a green and clean ammonia synthesis method.

[0003] Radiation catalytic nitrogen fixation, especially photocatalytic nitrogen fixation technology, has the advantages of high efficiency, cleanliness and high selectivity, and has attracted widespread attention. Humans can use catalysts with vacancies on the surface, such as modified TiO2, to convert nitrogen into ammonia, but so far, the capture and activation of nitrogen still need to overcome great difficulties, and the efficiency of nitrogen fixation is still low.

[0004] Due to the plasmon effect, plasmon catalysts can achieve a great enhancement of local energy on the surface of nanostructures. Thus, under mild overall reaction conditions, catalytic reactions can be efficiently promoted, making reactions that cannot be achieved under normal temperature and pressure possible. The present invention utilizes the plasmon effect and uses cost-effective nanostructured catalysts to successfully synthesize ammonia under mild conditions and achieve a high ammonia yield. Summary of the invention

[0005] The present invention illustrates a novel artificial synthesis technology, which provides a unique method for producing ammonia by light radiation and / or thermal radiation using N2 from the atmosphere in the presence of a nanostructured catalyst.

[0006] One aspect of the present invention is a method for producing ammonia by energy radiation, comprising:

[0007] contacting the nanostructured catalyst with at least one nitrogen-containing source and at least one hydrogen-containing source, and

[0008] irradiating the nanostructured catalyst, the nitrogen-containing source, and the hydrogen-containing source to produce ammonia, wherein

[0009] The nanostructured catalyst comprises at least one first component and at least one second component, and the distance between the first component and the second component is less than or equal to 200 nm, preferably less than or equal to 100 nm, and most preferably the two are in close contact,

[0010] The first component is selected from the group consisting of Co, Ni, Ru and alloys of two or more chemical elements thereof, preferably Ru or Co.

[0011] The second component is selected from the group consisting of Co, Ru, Rh, La, Ce, Ni, Mo, Bi, V, C and their oxides, sulfides, carbides, hydroxides, chlorides, carbonates and bicarbonates, and is preferably Co.

[0012] In some embodiments, the energy radiation is selected from at least one of light radiation and heat radiation. In a preferred embodiment, the energy radiation is light radiation.

[0013] In certain embodiments, the nanostructured catalyst comprises a chemical element that serves as both the first component and the second component, or comprises two or more chemical elements, alloys, or compounds that serve as the first component or the second component, respectively.

[0014] In certain embodiments, the nanostructured catalyst is physically mixed with the at least one first component and the at least one second component.

[0015] In certain embodiments, the nanostructured catalyst provides the at least one first component and the at least one second component in one nanostructure.

[0016] In a preferred embodiment, the nanostructured catalyst comprises Co.

[0017] In a preferred embodiment, the nanostructured catalyst is a Co catalyst or a Co-Ru catalyst. In a preferred embodiment, the molar ratio of Co to Ru in the Co-Ru catalyst is 10:1 to 2000:1, preferably 100:1 to 1200:1, more preferably 120:1 to 600:1, and most preferably 150:1 to 300:1.

[0018] In certain embodiments, at least one dimension of the length, width, and height of the nanostructure is about 1 nm to about 1000 nm, preferably about 70 nm to about 1000 nm, about 100 nm to about 800 nm, or about 200 nm to about 500 nm.

[0019] In certain embodiments, the nanostructures are each independently about 1 nm to about 3000 nm in length, width, and height, preferably about 100 nm to about 3000 nm in length, about 500 nm to about 2500 nm in length, or about 1000 nm to about 2000 nm in length, and / or about 1 nm to about 1000 nm in width or height, about 70 nm to about 1000 nm in width, about 100 nm to about 800 nm in height, or about 200 nm to about 500 nm in height, or

[0020] Each of the nanostructures independently has an aspect ratio of about 1 to about 20, preferably about 1 to about 10, or about 2 to about 8.

[0021] In certain embodiments, the nanostructured catalyst is in the shape of a sphere, spike, flake, needle, blade, column, polyhedron, three-dimensional cone, cube, sheet, hemisphere, irregular three-dimensional shape, porous structure or any combination thereof.

[0022] In certain embodiments, a plurality of said nanostructures are arranged in a pattern on a substrate, preferably in a multilayer arrangement, or

[0023] A plurality of the nanostructures are randomly dispersed in the medium.

[0024] In certain embodiments, the energy radiation causes the reaction to proceed at a temperature between about 20°C and about 300°C, preferably about 30°C to about 300°C, about 40°C to about 300°C, about 80°C to about 300°C, about 100°C to about 280°C, about 110°C to about 280°C, about 120°C to about 270°C.

[0025] In some embodiments, the reaction is initiated using light radiation or heat radiation, and the reaction is continued using light radiation or heat radiation, wherein

[0026] The light radiation power of the light radiation is 200-1500W / m 2 , preferably 200-1000W / m 2 , most preferably 500-1000W / m 2 .

[0027] In certain embodiments, the light radiation increases the temperature of the nanostructured catalyst, the nitrogen-containing source, and the hydrogen-containing source, and is preferably the only source of increased temperature.

[0028] In some embodiments, the nitrogen source is selected from the group consisting of N2, air, ammonia, nitrogen oxides, nitro compounds, any combination thereof, or air, industrial flue gas, tail gas or emissions containing more than one of these nitrogen sources, preferably N2.

[0029] In certain embodiments, the hydrogen source is selected from water, H2, C 1-4 The group consisting of hydrocarbons and any combination thereof, or air, industrial flue gas, tail gas or emissions containing more than one of these hydrogen-containing sources, preferably water. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The ion chromatogram of the product solution after reaction using Co catalyst and thermal radiation is shown.

[0031] Figure 2The ion chromatogram of the product solution after reaction using Co-Ru catalyst and thermal radiation is shown.

[0032] Figure 3 The ion chromatogram of the product solution after reaction using Co catalyst and light irradiation is shown.

[0033] Figure 4 The ion chromatogram of the product solution after reaction using Co-Ru catalyst and light irradiation is shown. DETAILED DESCRIPTION

[0034] The present invention demonstrates that, unexpectedly, N2 and water can be converted into ammonia in the presence of plasmonic nanostructured catalysts using light radiation and / or thermal radiation as energy input.

[0035] Before further describing the present invention, certain terms used in the specification, examples, and appended claims are collected in the following sections. The definitions listed herein should be read and understood by those skilled in the art in light of the remainder of the present invention. Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs.

[0036] definition

[0037] As used herein, the term "catalyst" refers to a substance that exhibits the effect of increasing the rate of a chemical reaction by reducing the activation energy of the reaction. The rate-increasing effect is called "catalysis." Catalysts are not consumed in catalyzing reactions, so they can continue to catalyze further reactions of the reactants in small amounts.

[0038] As used herein, the term "plasmon donor" refers to a conductor whose real part of the dielectric constant is negative. When excited by electromagnetic radiation, a plasmon donor can provide surface plasmons.

[0039] The term "chemical element" as used herein refers to a chemical substance composed of atoms having the same number of protons in the nucleus. Specifically, a chemical element is an element recorded in the periodic table of chemical elements. Chemical elements include natural elements and synthetic elements. Chemical elements also include elements that have not yet been discovered and have more than 118 protons in their nuclei.

[0040] The term "alloy" as used herein refers to a mixture of metals or a mixture of metals and other elements. Alloys are defined by the metallic bonding properties. Alloys can be solid solutions of metallic elements (single phase) or mixtures of metallic phases (solutions of two or more).

[0041] The term "close contact" used in this article means that there is basically no gap between the two, for example, the distance between the two is less than or equal to one tenth, less than or equal to one twentieth of the length, width or height dimension of the nanostructure, or less than or equal to 1nm, less than or equal to 0.1nm, or basically 0nm.

[0042] The term “C 1-4 “Hydrocarbons” include C1, C2, C3 and C4 hydrocarbons, such as methane, ethane, n-propane, isopropane, n-butane and isobutane.

[0043] Nanostructured Catalysts

[0044] One aspect of the present invention is a nanostructured catalyst for use in a reaction to produce ammonia by energy radiation.

[0045] Without wishing to be bound by theory, the nanostructured catalysts of the present invention interact with reacting raw materials to lower the activation energy of the reaction, thereby enabling the reaction to be initiated by energy radiation and increasing the reaction rate.

[0046] The nanostructured catalyst of the present invention comprises two components: a first component and a second component. One component is a plasmon donor, and the other is a catalytic property donor. The plasmon donor provides surface plasmon resonance enhancement to the catalyst positioning area, and the catalytic property donor provides catalytic properties to the reaction of producing ammonia. Different plasmon donors have different plasmon enhancement strengths and activity lifespans. For example, noble metal elements such as Ru have high plasmon enhancement strengths and long activity lifespans. Common metal elements such as Co have low plasmon enhancement strengths and short activity lifespans. Different catalytic property donors also have different catalytic strengths and activity lifespans. For example, Ni has a medium catalytic effect but a long active time. Elements such as Co and its oxides have high catalytic strengths, but short lifespans. Metal carbides have good catalytic strengths, but short activity lifespans.

[0047] In the nanostructured catalyst of the present invention, the distance between the first component and the second component is less than or equal to 200 nm, preferably less than or equal to 100 nm, and most preferably the two are in close contact. If the distance between the first component and the second component is outside the above range, the two components cannot cooperate with each other to play a role, thereby failing to catalyze the energy radiation reaction of the present invention.

[0048] The first component is a conductor whose real part of dielectric constant is negative. It can be a pure substance (chemical element) or an alloy, and it can be selected from the group consisting of Co, Ni, Ru and alloys of two or more chemical elements thereof. For efficiency and cost reasons, Ru or Co is preferably used in the present invention.

[0049] The second component can be a pure substance (chemical element) or a compound, and it can be selected from the group consisting of Co, Ru, Rh, La, Ce, Ni, Mo, Bi, V, C and oxides, sulfides, carbides, hydroxides, chlorides, carbonates and bicarbonates thereof. Co is most preferably used in the present invention.

[0050] The first component and the second component can be randomly mixed or regularly mixed. In some embodiments, the nanostructured catalyst comprises a chemical element that is simultaneously the first component and the second component, or comprises two or more chemical elements, alloys or compounds that are each the first component or the second component. In some embodiments, the nanostructured catalyst is formed by a physical mixture of the at least one first component and the at least one second component. In a preferred embodiment, the at least one first component and the at least one second component of the nanostructured catalyst are provided in a nanostructure, for example, the first component and the second component form an alloy. Specifically, the nanostructured catalyst can be nanoparticles of the aforementioned elements, or nanoparticles of the aforementioned element alloys, as long as the nanoparticles can provide both plasmon properties and catalytic properties. In a preferred embodiment, the first component plays the role of plasmon, and the second component plays the role of catalytic properties.

[0051] From the above description, it is clear that some elements exhibit both plasmon properties and catalytic properties. Therefore, the plasmon donor and catalytic property donor of the nanostructured catalyst can be the same element, such as Co, Ni, Ru, etc., or can be an element and its oxides, chlorides, carbides, carbonates and bicarbonates, such as Co and CoC, etc.

[0052] Mixtures of different elements will change the properties of these plasmonic nanoparticle catalysts. For example, Co / Ru alloys will increase the active life and catalytic effect of the catalyst; Co / C will only increase the effect of the catalyst, but reduce the life. In the present invention, the most preferred element combination of the nanostructured catalyst is Co / Ru, which has a better active life and catalytic effect of catalyzing the production of ammonia, such as ammonia yield, than other catalysts, and is cost-effective. In the present invention, other preferred catalysts include Co, which is cost-effective.

[0053] Nanostructure

[0054] As used herein, the term "nanostructure" refers to a structure having a size range of nanometer scale, i.e., at least one dimension of length, width, and height is from about 1 nm to about 1000 nm, preferably from about 70 nm to about 1000 nm, from about 100 nm to about 800 nm, from about 200 nm to about 500 nm. The nanostructure can have a dimension exceeding 1000 nm, for example, having a length in the micrometer scale range, such as 1 μm to 5 μm. In some cases, tubular objects and fibers having only two dimensions in the nanometer range are also considered nanostructures. Materials having nanostructures can present size-related properties that are significantly different from those observed in bulk materials.

[0055] The nanostructures of the present invention are each independently about 1 nm to about 3000 nm in length, width and height. The length is preferably about 100 nm to about 3000 nm, more preferably about 500 nm to about 2500 nm, and even more preferably about 1000 nm to about 2000 nm. The width or height is preferably about 1 nm to about 1000 nm, preferably about 70 nm to about 1000 nm, more preferably about 100 nm to about 800 nm, and even more preferably about 200 nm to about 500 nm.

[0056] The nanostructures of the present invention each independently have an aspect ratio (i.e., the ratio of length to width / height) of about 1 to about 20, preferably an aspect ratio of about 1 to about 10, or about 2 to about 8. The nanostructures of the present invention can also have a relatively low aspect ratio, such as about 1 to about 2.

[0057] The nanostructures of the present invention each independently have the following shapes: sphere, spike, flake, needle, blade, column, polyhedron, three-dimensional cone, cube, sheet, hemisphere, irregular three-dimensional shape, porous structure or any combination thereof.

[0058] Multiple nanostructures of the present invention can be arranged in a patterned configuration on a substrate, preferably in a multilayer arrangement, or multiple nanostructures can be randomly dispersed in a medium. For example, the nanostructures can be attached to a substrate. In this case, the nanostructures are generally not aggregated with each other, but are arranged or stacked in a regular form. Alternatively, multiple nanostructures can be dispersed in a liquid medium, wherein each nanostructure can move freely relative to other nanostructures.

[0059] For example, the nanostructure can have a spike-like or blade-like geometry. Optionally, the nanostructure is a thin sheet-like geometry with a relatively thin thickness. Preferably, the nanostructure has a nano-jungle, nano-grass, and / or nano-snowflake structure. The nanostructure can have a relatively large aspect ratio, and such a nanostructure can adopt the structure of a nano-spike, a nano-snowflake, or a nano-needle. The aspect ratio can be about 1 to about 20, about 1 to about 10, or about 2 to about 8. Preferably, the length of the nanostructure can be about 100nm to about 3000nm, about 500nm to about 2500nm, or about 1000nm to about 2000nm; the width or height can be about 1nm to about 1000nm, about 70nm to about 1000nm, about 100nm to about 800nm, or about 200nm to about 500nm.

[0060] The nanostructures may be bound to a matrix. Thus, the nanostructures are not generally aggregated together, but are arranged in an ordered manner. The matrix may be formed of a metal or a polymer material (eg, polyimide, PTFE, polyester, polyethylene, polypropylene, polystyrene, polyacrylonitrile, etc.).

[0061] In other examples, the nanostructure has a spherical, cylindrical, polyhedral, three-dimensional cone, cubic, lamellar, hemispherical, irregular three-dimensional shape, porous structure or any combination thereof. Such nanostructures are each independently about 1 nm to about 1000 nm in length, width and height, about 70 nm to about 1000 nm, about 100 nm to about 800 nm, or about 200 nm to about 500 nm. Plasmon donors and catalytic property donors can be mixed randomly or regularly. The distance between the plasmon donor and the catalytic property donor is less than 200 nm, preferably less than 100 nm, and more preferably the two are in close contact. In a preferred embodiment, the two components are provided in a nanostructure, for example, the nanostructure is an alloy of two or more chemical elements.

[0062] In addition, the nanostructure catalyst of the present invention can function in various states, such as dispersed, aggregated, or attached / grown on the surface of other materials. In a preferred embodiment, the nanostructure is dispersed in a medium, which is preferably a reactant of the reaction, such as water.

[0063] Methods of producing ammonia

[0064] Another aspect of the present invention is a method for producing ammonia by energy radiation, comprising:

[0065] contacting the nanostructured catalyst with at least one nitrogen-containing source and at least one hydrogen-containing source, and

[0066] Energy is radiated to the nanostructured catalyst, the nitrogen-containing source, and the hydrogen-containing source to produce ammonia.

[0067] Under the catalytic action of the nanostructured catalyst, energy radiation, i.e., light radiation and / or heat radiation, triggers the reaction of the nitrogen-containing source and the hydrogen-containing source. Without being bound by theory, the nanostructured catalyst can convert and transfer the energy of light radiation and heat radiation, thereby allowing the reaction of the present invention to continue.

[0068] The energy radiation allows the reaction to be carried out at a temperature between about 20°C and about 300°C, preferably about 30°C to about 300°C, about 40°C to about 300°C, about 80°C to about 300°C, about 100°C to about 280°C, about 110°C to about 280°C, about 120°C to about 270°C.

[0069] At temperatures between about 20°C and about 300°C, the reaction has an ammonia yield greater than 10 μmol.

[0070] As used herein, the term "heat" refers to heat energy transferred from one system to another as a result of heat exchange. Heat energy can be transferred to the reaction system from an external heat source, or it can be carried by one reaction component and transferred to other reaction components. In other words, the reaction component that carries heat energy before the reaction is also referred to as an internal heat source. In certain embodiments, thermal radiation increases the temperature of the nanostructured catalyst, the nitrogen-containing source, and the hydrogen-containing source in the reaction of the present invention.

[0071] In the reaction of the present invention, the light radiation simulates the wavelength composition and intensity of sunlight, so it can increase the temperature of the irradiated catalyst and reaction mixture. When the radiation intensity reaches a certain level, the temperature of the nanostructured catalyst, nitrogen source and hydrogen source is increased by light radiation.

[0072] In the reaction of the present invention, the light radiation increases the temperature of the nanostructured catalyst, the nitrogen-containing source and the hydrogen-containing source, and is preferably the only source of increasing the temperature.

[0073] In the reaction of the present invention, the term "light" as used herein refers to electromagnetic waves with a wavelength between about 250 nm and about 2000 nm. In other words, light refers to the radiation of visible light. Preferably, in the reaction of the present invention, the light radiation power is lower than the solar radiation power (i.e., the solar constant). For example, the light radiation power is 200-1500 W / m 2 , preferably 200-1000W / m 2 , most preferably 500-1000W / m 2 The light radiation may be sunlight or light emitted by an artificial light source, and the wavelength of the light radiation is between about 250 nm and about 2000 nm.

[0074] The reaction time varies according to the size of the reaction, the radiation intensity, the temperature and other factors, and the reaction is carried out continuously using a complete apparatus and continuously adding the nitrogen-containing source and the hydrogen-containing source. The reaction time can be more than 0.1 hours, preferably 0.1 hours to 1000 hours, preferably 0.1 hours to 500 hours, preferably 0.5 hours to 100 hours, preferably 1 hour to 50 hours, preferably 2 hours to 30 hours, and most preferably 4 hours to 20 hours.

[0075] The reaction can be carried out under low pressure, normal pressure or high pressure, and the appropriate reaction pressure can be selected according to the size of the reaction, radiation intensity, temperature and other factors. For example, the reaction pressure can be at least 1 bar, such as 1 bar to 30 bar, preferably 1 bar to 20 bar, and more preferably 1.5 bar to 5 bar.

[0076] Reaction materials

[0077] In the reaction of the present invention, the reaction raw materials include a nitrogen source and a hydrogen source.

[0078] The nitrogen source is selected from the group consisting of N2, air, ammonia, nitrogen oxides, nitro compounds and any combination thereof, or air, industrial flue gas, tail gas or emissions containing one or more of these nitrogen sources. In the reaction of the present invention, the nitrogen source is preferably N2.

[0079] The hydrogen source is selected from water, H2, C 1-4 The group consisting of hydrocarbons and any combination thereof, or air, industrial flue gas, tail gas or emissions containing more than one of these hydrogen-containing sources. In the reaction of the present invention, the hydrogen-containing source is preferably water; the water can be in gaseous or liquid state.

[0080] It can be seen from the above-mentioned reaction raw materials that the nitrogen-containing source and hydrogen-containing source that can be used in the present invention are widely present in industrial waste gas, waste water, flue gas, combustion emissions and automobile exhaust, etc., so they can be used as the reaction raw materials of the present invention, which is beneficial to the recycling of industrial waste.

[0081] Reaction products

[0082] The reaction of the present invention can produce ammonia. Without wishing to be bound by theory, the reaction mechanism of the present invention may include the decomposition and recombination of various reaction raw material molecules on the nanostructure of the plasmonic metal catalyst.

[0083] Example

[0084] Example 1 Preparation of Nanostructured Catalyst

[0085] The Co catalyst was prepared by the following method:

[0086] In a 250mL three-necked flask, add 8.1g of cobalt chloride hexahydrate (CoCl2·6H2O), add 100mL of water, stir to dissolve, and heat to 80℃ to condense and reflux; dissolve 10.88g of sodium hydroxide (NaOH) in 30mL of water, add 30mL of hydrazine hydrate (N2H4·H2O), and then use a titration pump to control the mixture to 1.8mL min -1 The solution was slowly dripped into a three-necked flask at a speed of . After reacting for 60 minutes, the solution was cooled to room temperature, separated by a 5000 rpm centrifuge for 5 minutes, ultrasonically washed with deionized water 3 times, and dried in a vacuum oven at 70°C to obtain the Co catalyst used in the experiment. SEM characterization showed that the Co catalyst was in the form of Co nanoparticles with a particle size of about 100 nm.

[0087] The Co-Ru catalyst was prepared by the following method:

[0088] In a 250mL three-necked flask, add 8.1g of cobalt chloride hexahydrate (CoCl2·6H2O) and 0.042g of ruthenium trichloride (RuCl3·xH2O), add 100mL of water, stir to dissolve, and heat to 80℃ to condense and reflux; dissolve 10.88g of sodium hydroxide (NaOH) in 30mL of water, add 30mL of hydrazine hydrate (N2H4·H2O), and then use a titration pump to control the mixture to 1.8mL min -1 The solution was slowly dripped into a three-necked flask at a speed of . After reacting for 60 minutes, the solution was cooled to room temperature, separated by a 5000 rpm centrifuge for 5 minutes, ultrasonically washed with deionized water 3 times, and dried in a vacuum oven at 70°C to obtain the Co-Ru catalyst used in the experiment. SEM characterization showed that the Co-Ru catalyst was in the form of nanoparticles with a particle size of about 200 nm, including Co nanoparticles, Ru nanoparticles and Co-Ru alloy nanoparticles.

[0089] Example 2 Thermal catalytic reaction of producing ammonia using Co

[0090] Add 1.9g Co catalyst and 6mL ultrapure water to a 35mL sealable pressure-bearing glass tube, exhaust the air inside with N2, and fill with 4bar N2. Wrap the glass tube with multiple layers of aluminum foil to isolate it from light. Place the glass tube in a temperature-controlled oven and heat it to react. Control the temperature in the oven to 135℃±5℃ and continue the reaction for 18h.

[0091] After the thermal catalytic reaction, the solution in the reaction tube was cooled to room temperature by standing, and the supernatant was obtained by centrifugation. The NH4 + Content, with the configured 5ppm NH4 +The standard solution was compared with a CG12 (2×50 mm) guard column and a CS12 (4×250 mm) analytical column at a flow rate of 1.2 mL / min, an inhibition current of 71 mA, and a column temperature of 30°C.

[0092] The product ion chromatogram obtained after the thermal catalytic reaction using Co catalyst is shown in Figure 1 Compared with NH4 + Standard solution, NH4 + The content is 3.17ppm. The ammonia production is calculated to be 11.40μmol.

[0093] After the above reaction was continuously carried out for 80 hours, the catalytic activity of the Co catalyst in producing ammonia did not decrease.

[0094] Example 3 Thermal catalytic reaction of ammonia production using Co-Ru catalyst

[0095] A thermal catalytic reaction was carried out in the same manner as in Example 2 using a Co-Ru catalyst.

[0096] The solution after the reaction was characterized by ion chromatography in the same manner as in Example 2. The product ion chromatogram obtained after the thermal catalytic reaction using the Co-Ru catalyst is as follows: Figure 2 As shown, NH4 is calculated + The content was 3.11 ppm and the ammonia production was 10.99 μmol.

[0097] After the above reaction was continuously carried out for 80 hours, the catalytic activity of the Co-Ru catalyst in producing ammonia did not decrease.

[0098] Example 4 Photocatalytic reaction of producing ammonia using Co

[0099] 1.9g Co catalyst and 6mL ultrapure water were added to a 35mL sealed pressure-bearing glass tube, and the air inside was expelled with N2, and 4bar N2 was filled in. The glass tube was placed flat on glass wool to evenly spread the catalyst and water, and a voltage-controlled halogen lamp was used to illuminate vertically from above. The incident light intensity was about 1000W / m 2 A thermocouple was connected to the lower part of the glass tube to monitor the temperature. The temperature of the glass tube was controlled at 135°C ± 5°C and the light was continuously irradiated for 18 h to carry out the photocatalytic reaction.

[0100] The solution after the reaction was characterized by ion chromatography in the same manner as in Example 2. The product ion chromatogram obtained after the photocatalytic reaction using the Co catalyst is as follows: Figure 3 As shown, the ammonia content was calculated to be 6.99 ppm and the ammonia production was 52.63 μmol.

[0101] After the above reaction was continuously carried out for 80 hours, the catalytic activity of the Co catalyst in producing ammonia did not decrease.

[0102] Example 5 Photocatalytic reaction of producing ammonia using Co-Ru catalyst

[0103] A photocatalytic reaction was carried out in the same manner as in Example 4 using a Co—Ru catalyst.

[0104] The solution after the reaction was characterized by ion chromatography in the same manner as in Example 2. The product ion chromatogram obtained after the photocatalytic reaction using the Co-Ru catalyst is as follows: Figure 4 As shown, NH4 is calculated + The content was 22.36 ppm and the ammonia production was 522.35 μmol.

[0105] After the above reaction was continuously carried out for 80 hours, the catalytic activity of the Co-Ru catalyst in producing ammonia did not decrease.

[0106] The results of Examples 2 to 5 show that the method of the present invention is able to efficiently convert readily available raw materials into high-value ammonia products under mild overall reaction conditions, under thermal radiation and / or relatively low-intensity light radiation, and at a reaction temperature below 300°C using a cost-effective catalyst.

[0107] In this specification and the appended claims, the singular forms "a", "an", and "the" include plural forms unless the context clearly dictates otherwise. Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. The methods described herein may be performed in any order that is logically possible, except for the specific order disclosed.

[0108] The representative examples are intended to help illustrate the present invention and are not intended to, nor should they be construed as, limiting the scope of the present invention. In fact, various modifications of the present invention and many other embodiments thereof, in addition to those shown and described herein, will become apparent to those skilled in the art, including the examples and scientific and patent literature references cited herein. The examples contain important additional information, illustrations and guidance that can be practiced by the present invention in its various embodiments and equivalents.

Claims

1. A method for producing ammonia by energy radiation, comprising: contacting the nanostructured catalyst with at least one nitrogen-containing source and at least one hydrogen-containing source, and irradiating the nanostructured catalyst, the nitrogen-containing source, and the hydrogen-containing source to produce ammonia, wherein The nanostructured catalyst comprises at least one first component and at least one second component, and the distance between the first component and the second component is less than or equal to 200 nm, The first component is selected from the group consisting of Co, Ni, Ru and alloys of two or more chemical elements thereof, The second component is selected from the group consisting of Co, Ru, Rh, La, Ce, Ni, Mo, Bi, V and oxides, sulfides, carbides, hydroxides, chlorides, carbonates and bicarbonates thereof, The energy radiation causes the reaction to proceed at a temperature between 120°C and 270°C. The reaction pressure is 4 bar to 5 bar, and The hydrogen source is water. 2 . The method of claim 1 , wherein a distance between the first component and the second component is less than or equal to 100 nm.

3. The method of claim 1, wherein the first component and the second component are in intimate contact. The method of claim 1 , wherein the first component is Ru or Co. The method of claim 1 , wherein the second component is Co.

6. The method of claim 1, wherein The energy radiation is selected from at least one of light radiation and heat radiation. The method of claim 6 , wherein the energy radiation is light radiation.

8. The method according to any one of claims 1 to 7, wherein The nanostructured catalyst comprises a chemical element serving as both the first component and the second component, or comprises two or more chemical elements, alloys or compounds serving as the first component or the second component respectively.

9. The method according to any one of claims 1 to 7, wherein The nanostructured catalyst is physically mixed with the at least one first component and the at least one second component.

10. The method according to any one of claims 1 to 7, wherein The nanostructured catalyst provides the at least one first component and the at least one second component in one nanostructure.

11. The method according to any one of claims 1 to 7, wherein The nanostructured catalyst comprises Co.

12. The method according to any one of claims 1 to 7, wherein The nanostructured catalyst is a Co catalyst or a Co-Ru catalyst.

13. The method of claim 12, wherein The molar ratio of Co to Ru in the Co-Ru catalyst is 10:1 to 2000:

1.

14. The method of claim 12, wherein the molar ratio of Co to Ru in the Co-Ru catalyst is 100:1 to 1200:

1.

15. The method of claim 12, wherein the molar ratio of Co to Ru in the Co-Ru catalyst is 120:1 to 600:

1.

16. The method of claim 12, wherein the molar ratio of Co to Ru in the Co-Ru catalyst is 150:1 to 300:

1.

17. The method according to any one of claims 1 to 7, wherein At least one dimension of the length, width and height of the nanostructure is 1 nm to 1000 nm.

18. The method according to any one of claims 1 to 7, wherein at least one dimension of the length, width and height of the nanostructure is 70 nm to 1000 nm.

19. The method according to any one of claims 1 to 7, wherein at least one dimension of the length, width and height of the nanostructure is in the range of 100 nm to 800 nm.

20. The method of any one of claims 1 to 7, wherein at least one dimension of the length, width, and height of the nanostructure is 200 nm to 500 nm.

21. The method according to any one of claims 1 to 7, wherein The length, width and height of the nanostructures are independently 1 nm to 3000 nm, or The nanostructures each independently have an aspect ratio of 1 to 20.

22. The method of claim 21, wherein the nanostructure has a length of 100 nm to 3000 nm.

23. The method of claim 21, wherein the nanostructure has a length of 500 nm to 2500 nm.

24. The method of claim 21, wherein the nanostructure has a length of 1000 nm to 2000 nm.

25. The method of claim 21, wherein the nanostructure has a width or height of 70 nm to 1000 nm.

26. The method of claim 21, wherein the nanostructure has a width or height of 100 nm to 800 nm.

27. The method of claim 21, wherein the width or height of the nanostructure is 200 nm to 500 nm.

28. The method of claim 21, wherein the nanostructures each independently have an aspect ratio of 1 to 10.

29. The method of claim 21, wherein the nanostructures each independently have an aspect ratio of 2 to 8.

30. The method of any one of claims 1 to 7, wherein The nanostructured catalyst is in the shape of a sphere, spike, flake, needle, blade, column, polyhedron, three-dimensional cone, cube, sheet, hemisphere, irregular three-dimensional shape, porous structure or any combination thereof.

31. The method of any one of claims 1 to 7, wherein A plurality of said nanostructures are arranged in a pattern on a substrate, or A plurality of the nanostructures are randomly dispersed in the medium.

32. The method of claim 31, wherein a plurality of said nanostructures are arranged in multiple layers on a substrate.

33. The method of claim 6 or 7, wherein The reaction is initiated using light radiation or heat radiation, and the reaction is continued using light radiation or heat radiation, wherein The light radiation power of the light radiation is 200-1500W / m 2 .

34. The method of claim 33, wherein the optical radiation power of the optical radiation is 200-1000 W / m 2 .

35. The method of claim 33, wherein the optical radiation power of the optical radiation is 500-1000 W / m 2 .

36. The method of claim 6 or 7, wherein The light radiation increases the temperature of the nanostructured catalyst, the nitrogen-containing source, and the hydrogen-containing source.

37. The method of claim 36, wherein the optical radiation is the only source for increasing the temperature of the nanostructured catalyst, the nitrogen-containing source, and the hydrogen-containing source.

38. The method of any one of claims 1 to 7, wherein The nitrogen source is selected from the group consisting of N2, air, ammonia, nitrogen oxides, nitro compounds, any combination thereof, or air, industrial flue gas, tail gas or emissions containing more than one of these nitrogen sources.

39. The method of any one of claims 1 to 7, wherein the nitrogen-containing source is N2.

Citation Information

Patent Citations

  • KR20190128312A